Sonographic Accuracy as a Novel Tool for Point‐of‐care Ultrasound Competency Assessment. Issue 4 (27th September 2017) - Bell, Colin R.; McKaigney, Conor J.; Holden, Matthew; Fichtinger, Gabor; Rang, Louise
Abstract: Objectives: The Focused Assessment with Sonography in Trauma (FAST) is a point‐of‐care ultrasound (PoCUS) study that is routine in trauma patient assessment. Many organizations have published training guidelines, which grant competency through the completion of a fixed number of observed scans. This approach is incongruent with current trends in competency‐based medical education. We aim to objectively quantify probe motion and user accuracy to differentiate groups of PoCUS operators. Methods: Emergency medicine residents were recruited in two groups. The novice group ( n =  15) had limited PoCUS experience, whereas the intermediate group ( n =  14) had completed at least 50 supervised FAST examinations. Both groups underwent assessment on a live human model. Residents from the novice group returned ( n =  9) after completing a curriculum and repeated the assessment using the identical experimental construct. Results: Significant differences (p < 0.05) were found between the novice and both the intermediate and the novice returned groups in time, path length, and points of interest (POIs) scanned. Novices required more time to complete the full examination (290.82 seconds vs. 197.41 seconds vs. 271.79 seconds), utilized more motion (9392.07 mm vs. 4052.73 mm vs. 4985.05 mm), and imaged fewer POIs (48.13% vs. 95.00% vs. 100.00%) when compared to intermediates and returning novices, respectively. No difference was found between the intermediate and novice returned groups for the complete examination. Spearman's correlation was calculated between variables within each group. Correlations between time and path length were statistically significant (p < 0.05) with novice, intermediate, and novice returned values of 0.67, 0.65, and 0.90. Interestingly, neither time nor path length consistently correlated with POIs scanned in any group. Conclusion: Differences in probe motion efficiency and POIs scanned between novices and intermediate or returning novice users show promise for use as a quantitative objective assessment tool. Unlike in surgical literature, accuracy did not correlate with path length or time to examination completion.